1997
DOI: 10.1210/mend.11.4.9906
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Activates Mutant Androgen Receptors Expressed in the Androgen-Dependent Human Prostate Cancer Xenograft CWR22 and LNCaP Cells

Abstract: An androgen receptor (AR) gene mutation identified in the androgen-dependent human prostate cancer xenograft, CWR22, changed codon 874 in the ligand-binding domain (exon H) from CAT for histidine to TAT for tyrosine and abolished a restriction site for the endonuclease SfaNI. SfaNI digestion of AR exon H DNA from normal but not from prostate cancer tissue indicated H874Y is a somatic mutation that occurred before the initial tumor transplant. CWR22, an epithelial cell tumor, expresses a 9.6-kb AR mRNA similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(68 citation statements)
references
References 45 publications
0
67
0
1
Order By: Relevance
“…1, lanes 1-3). Full-length AR was also evident in extracts of the CWR22 human prostate cancer xenograft propagated in nude mice (Wainstein et al 1994, Nagabhushan et al 1996, Tan et al 1997) from both androgen-dependent tumors and recurrent tumors that arose after prolonged androgen deprivation by castration (Fig. 1, lanes 5-6).…”
Section: Ar In Cell Lines and Tissuesmentioning
confidence: 92%
“…1, lanes 1-3). Full-length AR was also evident in extracts of the CWR22 human prostate cancer xenograft propagated in nude mice (Wainstein et al 1994, Nagabhushan et al 1996, Tan et al 1997) from both androgen-dependent tumors and recurrent tumors that arose after prolonged androgen deprivation by castration (Fig. 1, lanes 5-6).…”
Section: Ar In Cell Lines and Tissuesmentioning
confidence: 92%
“…The mutation is located in exon H of the AR gene and leads to an exchange of the wild-type threonine (position 877) to alanine. It has been demonstrated in several studies that hormones that bind to the mutated LNCaP AR with increased affinity stimulate cellular proliferation and enhance transcriptional activation function of that AR (Veldscholte et al 1990a,b, 1992, Montgomery et al 1992, Tan et al 1997. These hormones are estrogenic and progestagenic steroids, adrenal androgens, and the non-steroidal antiandrogens hydroxyflutamide and nilutamide.…”
Section: Ar Structural Alterations In Prostate Cancermentioning
confidence: 99%
“…Transcription activation function of the MDA PCa 2a AR is strongly induced by the glucocorticoid hormones, cortisol and cortisone (Zhao et al 2000), which promote the growth of that cell line. In the prostate cancer xenograft CWR 22, there is an exchange of histidine at position 874 with tyrosine (Tan et al 1997). Histidine 874 does not contact ligand and the mutation found in the prostate cancer xenograft most probably affects binding of AR coactivators and their regulation of AR function (McDonald et al 2000).…”
Section: Ar Structural Alterations In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The other major phenotypic output of common LBD mutations is antagonist-agonist switching (Supplementary Table 1), which likely explains the withdrawal syndrome observed after cessation of firstgeneration antagonists seen in 15-30% of patients (Small et al 2004). T878A confers agonist properties to flutamide and nilutamide, H875Y to nilutamide and W742C/L to bicalutamide (Veldscholte et al 1990, Suzuki et al 1996, Tan et al 1997, Hara et al 2003, Azad et al 2015, O'Neill et al 2015, Lallous et al 2016. Interestingly, O'Neill and coworkers recently demonstrated that T878A inhibited bicalutamide-activated W742L (O'Neill et al 2015) in what may represent the first evidence of antagonism arising from the heterodimerization of distinct AR mutants.…”
Section: Gata2 Oct1mentioning
confidence: 99%